ANALISIS KEUNGGULAN KOMPARATIF EKSPOR PRODUK BERBASIS KELAPA SULAWESI UTARA - Alan Kawa; Caroline B.D. Pakasi; Juliana R Mandei (COCOS, 2016)
ABSTRACTThe aim of this research is to analyze the comparative advantage of coconut-based products export in North Sulawesi from 2006 to 2015. Data used in this research is secondary data, which is come from the previous researched and various literature. Data are also obtained from relevant agencies, such as the Asian Pacific Coconut Community (APCC) Jakarta and from relevant agencies, Department of Industry and Commerce of North Sulawesi, Central Bureau of Statistics of North Sulawesi, Department of Agriculture of North Sulawesi and Department of Plantation of North Sulawesi. Revealed Comparative Advantage (RCA) method is used in this research. The results showed that all exports of coconut-based products during 2006-2015 have comparative advantage and have strong competitiveness, except in the year 2014-2015 charcoal and copra products experienced a decline in competitiveness.Keywords : Export, Competitiveness, Comparative Advantage.